853PARCHES - The role of androgen deprivation therapy (ADT) with enzalutamide (ENZA) or placebo (PBO) in metastatic hormone-sensitive prostate cancer (mHSPC): Post hoc analyses of high and low disease volume and risk groups. (1st October 2019) - Stenzl, A; Szmulewitz, R Z; Petrylak, D P; Holzbeierlein, J; Villers, A; Azad, A A; Alcaraz, A; Alekseev, B Y; Iguchi, T; Shore, N D; Rosbrook, B; Baron, B; et al.
Abstract: Background: ENZA, a potent androgen receptor inhibitor, provides benefit in men with castration-resistant prostate cancer (CRPC). In post hoc analyses, the role of ENZA + ADT in mHSPC patients (pts) randomized within the multinational, double-blind, PBO-controlled, Phase 3 ARCHES study (NCT02677896) was determined by disease volume and risk group stratification. Methods: mHSPC pts were randomized 1:1 to ENZA (160 mg/day) + ADT or PBO + ADT. The primary endpoint was radiographic progression-free survival (rPFS). Secondary endpoints included prostate-specific antigen (PSA) progression and radiographic responses, overall survival (OS), and quality of life (QoL). Analyses were completed by CHAARTED-defined disease volume and LATITUDE-defined risk groups. Results: 1150 pts were randomized (ENZA + ADT, n = 574; PBO + ADT, n = 576). Median follow-up was 14.4 months. ENZA + ADT significantly improved rPFS (hazard ratio [95% CI] 0.39 [0.30, 0.50]; p < 0.0001). ENZA + ADT pts significantly benefited from prolonged rPFS in all subgroups (Table). Significant treatment benefits were observed with ENZA + ADT in several secondary clinical endpoints in the overall population and in both high and low disease volume and risk groups (Table). High QoL at baseline was maintained over time. OS data are immature. Adverse events (AEs) were reported in 85.1% of ENZA + ADT vs. 85.9% of PBO + ADT pts, with no unexpected AEs. Conclusions: ENZA + ADT treatment showed efficacy benefit across all mHSPC pts, irrespective of disease volume and risk group. Similar delays in rPFS, symptomatic skeletal events, PSA progression, castration resistance, and improvements in radiographic responses and PSA declines, with maintenance of high QoL over time, were observed. Preliminary safety analysis appears consistent with the safety profile of ENZA in previous CRPC clinical trials. Clinical trial identification: NCT02677896. Editorial acknowledgement: Beatrice Vetter-Ceriotti and Lauren Smith from Complete HealthVizion, funded by the study sponsors. Legal entity responsible for the study: Astellas Pharma Inc. and Medivation LLC, a Pfizer Company, the co-developers of enzalutamide. Funding: Astellas Pharma Inc. and Medivation LLC, a Pfizer Company, the co-developers of enzalutamide. Disclosure: A. Stenzl: Advisory / Consultancy: Bipsen Pharma; Advisory / Consultancy: Roche; Advisory / Consultancy, Research grant / Funding (self), Travel / Accommodation / Expenses: Janssen; Advisory / Consultancy: Alere; Advisory / Consultancy: BMS; Advisory / Consultancy: Stebatiotechnology; Research grant / Funding (self): Karl Storz AG; Research grant / Funding (self): Astellas Pharma; Research grant / Funding (self): AstraZeneca; Research grant / Funding (self): Medivation; Travel / Accommodation / Expenses: Ipsen Pharma; Travel / Accommodation / Expenses: Sanofi; Travel / Accommodation / Expenses: Aventis; Travel / Accommodation / Expenses: Curevac; Travel / Accommodation / Expenses: Ferring. R.Z. Szmulewitz: Advisory / Consultancy: AstraZeneca; Advisory / Consultancy, Research grant / Funding (self): AbbVie; Advisory / Consultancy: Exelixis; Advisory / Consultancy: Merck; Advisory / Consultancy: Amgen; Advisory / Consultancy, Research grant / Funding (self): Janssen Oncology; Advisory / Consultancy: Sanofi; Advisory / Consultancy, Research grant / Funding (self): Astellas Pharma; Advisory / Consultancy: Pfizer; Research grant / Funding (self): Incyte; Research grant / Funding (self): Macrogenics; Travel / Accommodation / Expenses: Concept Therapeutics. D.P. Petrylak: Advisory / Consultancy, Shareholder / Stockholder / Stock options: Bellicum; Shareholder / Stockholder / Stock options: Tyme; Advisory / Consultancy: Astellas Pharma; Advisory / Consultancy, Research grant / Funding (institution): AstraZeneca; Advisory / Consultancy, Research grant / Funding (institution): Bayer; Research grant / Funding (institution): Genentech; Research grant / Funding (institution): Merck; Advisory / Consultancy: Exelixis; Advisory / Consultancy: Ferring; Advisory / Consultancy, Research grant / Funding (institution): Johnson & Johnson; Speaker Bureau / Expert testimony: Celgene; Advisory / Consultancy, Research grant / Funding (institution): Medivation, Lilly; Advisory / Consultancy, Research grant / Funding (institution): Millineum, Dendreon, Aventis; Research grant / Funding (institution): Progenics; Advisory / Consultancy, Research grant / Funding (institution): Roche Laboratories; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution): Sanofi; Research grant / Funding (institution): Innocrin; Research grant / Funding (institution): Agensys; Research grant / Funding (institution): Clovis; Research grant / Funding (institution): Endocyte; Advisory / Consultancy, Research grant / Funding (institution): Pfizer. J. Holzbeierlein: Research grant / Funding (self): Astellas Pharma; Research grant / Funding (self): MDX Health. A. Villers: Advisory / Consultancy: Astellas France; Research grant / Funding (institution): Astellas Pharma. A.A. Azad: Advisory / Consultancy, Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Astellas Pharma; Advisory / Consultancy, Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Novartis; Advisory / Consultancy, Travel / Accommodation / Expenses: Janssen; Advisory / Consultancy: Sanofi; Advisory / Consultancy: AstraZeneca; Advisory / Consultancy, Travel / Accommodation / Expenses: Pfizer; Advisory / Consultancy: Bristol-Myers Squibb; Advisory / Consultancy, Travel / Accommodation / Expenses: Tolmar; Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Amgen; Speaker Bureau / Expert testimony: Bayer; Advisory / Consultancy, Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Novartis. A. Alcaraz: Travel / Accommodation / Expenses: Astellas; Travel / Accommodation / Expenses: Olympus; Travel / Accommodation / Expenses: Ipsen. B.Y. Alekseev: Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (self), Travel / Accommodation / Expenses: AstraZeneca; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (self), Travel / Accommodation / Expenses: Astellas Pharma; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (self), Travel / Accommodation / Expenses: Bayer; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (self), Travel / Accommodation / Expenses: BMS; Advisory / Consultancy, Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Ferring; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (self), Travel / Accommodation / Expenses: Janssen; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (self), Travel / Accommodation / Expenses: MSD; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (self), Travel / Accommodation / Expenses: Pfizer; Advisory / Consultancy, Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Sanofi. T. Iguchi: Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution): Bayer; Advisory / Consultancy, Speaker Bureau / Expert testimony: Janssen; Speaker Bureau / Expert testimony, Research grant / Funding (institution): Astellas Pharma; Speaker Bureau / Expert testimony: Sanofi; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution): Bayer. N.D. Shore: Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution), Travel / Accommodation / Expenses: Bayer; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution), Travel / Accommodation / Expenses: Janssen Scientific Affairs; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution), Travel / Accommodation / Expenses: Dendreon; Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: Tolmar; Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: Ferring; Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: Medivation/Astellas; Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: Amgen; Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: Pfizer; Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: AstraZeneca; Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: Genentech/Roche; Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: Myovant Sciences; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution), Travel / Accommodation / Expenses: Bayer. B. Rosbrook: Shareholder / Stockholder / Stock options, Full / Part-time employment: Pfizer Inc. B. Baron: Advisory / Consultancy, Full / Part-time employment: Astellas. G.P. Haas: Full / Part-time employment: Astellas Pharma. R. Morlock: Advisory / Consultancy: Abbott Medical Optics; Advisory / Consultancy: Ironwood; Advisory / Consultancy: Genentech; Full / Part-time employment: Astellas Pharma. K. Ramaswamy: Shareholder / Stockholder / Stock options, Full / Part-time employment: Pfizer Inc. A.J. Armstrong: Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Sanofi; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution), Travel / Accommodation / Expenses: Dendreon; Honoraria (institution): Janssen Oncology; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution), Travel / Accommodation / Expenses: Bayer; Advisory / Consultancy, Research grant / Funding (institution): Novartis; Advisory / Consultancy, Research grant / Funding (institution): Medivation; Advisory / Consultancy, Travel / Accommodation / Expenses: Janssen Biotech; Advisory / Consultancy, Research grant / Funding (institution): Pfizer; Advisory / Consultancy, Travel / Accommodation / Expenses: Astellas Scientific & Medical Affairs Inc; Research grant / Funding (institution): Gilead Sciences; Research grant / Funding (institution): Roche/Genentech; Research grant / Funding (institution): Active Biotech; Research grant / Funding (institution): Bristol-Myers Squibb; Research grant / Funding (institution): Astellas Pharma; Research grant / Funding (institution): Janssen.